Photophysical studies on curcumin-sophorolipid nanostructures: applications in quorum quenching and imaging - Vasudevan, Sahana; Prabhune, Asmita A. (Royal Society Open Science, 2018)
Sophorolipid biosurfactants are biodegradable, less toxic and FDA approved. The purified acidic form of sophorolipid is stimuli-responsive with self-assembling properties and used for solubilizing hydrophobic drugs. This study encapsulated curcumin (CU) with acidic sophorolipid (ASL) micelles and analysed using photophysical studies like UV-visible spectroscopy, photoluminescence (PL) spectroscopy and timecorrelated single photon counting (TCSPC). TEM images have revealed ellipsoid micelles of approximately 100nm size and were confirmed by dynamic light scattering. The bacterial fluorescence uptake studies showed the uptake of formed CUASL nanostructures into both Gram-positive and Gram-negative bacteria. They also showed quorum quenching activity against Pseudomonas aeruginosa. The results have demonstrated this system has potential theranostic applications.
Keywords: curcumin; photophysical; Quorum quenching; Sophorolipid